Long-term follow-up of posterior capsule opacification after AquaLase and NeoSoniX phacoemulsification - Stepanov, Alexandr; Nekolova, Jana; Jiraskova, Nada; Rozsival, Pavel (Biomedical papers, 2016)
Aim: To compare the degree of posterior capsule opacification (PCO) after AquaLase and NeoSoniX phacoemulsification methods during an 8-year follow-up period using two types of software.Design: Prospective, randomized clinical trial.Methods: AquaLase was used in the right eye and NeoSoniX in the left eye of each patient with bilateral cataract.Results: Fifty patients were analyzed 1 year, 46 patients 3 years, and 37 patients 8 years after cataract surgery. Mean EPCO 2000 values were for the AquaLase group 0.324 ± 0.305 and for the NeoSoniX group 0.298 ± 0.341 (P = 0.53) 1 year after surgery, for the AquaLase group 0.582 ± 0.506 and for the NeoSoniX group 0.594 ± 0.515 (P = 0.87) 3 years after surgery, and for the AquaLase group 0.648 ± 0.567 and for the NeoSoniX group 0.673 ± 0.542 (P = 0.30) 8 years after surgery. The OSCA results were for the AquaLase group 0.7097 ± 0.3778 and for the NeoSoniX group 0.8584 ± 0.4323 (P = 0.046) 1 year after surgery, for the AquaLase group 0.9667 ± 0.736 and for the NeoSoniX group 0.9540 ± 0.5250 (P = 0.91) 3 years after surgery, and for the AquaLase group 1,035 ± 0,952 and for the NeoSoniX group 1,103 ± 0,741 (P = 0.44) 8 years after surgery.Conclusion: There was minimal PCO difference between these 2 approaches, AquaLase and NeoSoniX. Neither AquaLase nor NeoSoniX technique was able to prevent a natural progression of PCO.
Keywords: posterior capsule opacification; AquaLase; NeoSoniX